Technology Adoption Among Small And Medium Enterprises (SME's): A Research Agenda. - Thurasamy, Ramayah; Mohamad, Osman; Omar, Azizah; Marimuthu, Malliga (2009)

(untitled)
This paper presents the research agenda that has been proposed to develop an integrated model to explain technology adoption of SMEs in Malaysia. SMEs form over 90% of all business entities in Malaysia and they have been contributing to the development of the nation.